2020
DOI: 10.3390/su12187737
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks Consumption and Addiction in College Students during the COVID-19 Pandemic: Educational Approach to Responsible Use

Abstract: Within the framework of digital sustainability, the increase in Internet consumption, and especially online social networks, offers social benefits, but is not without its drawbacks. For example, it can lead to psychological and/or psychiatric disorders in some people. Numerous researches are highlighting the similarities of these addictions with the consumption of toxic substances. University students are heavy users of the Internet and, in certain situations, addiction to online social networks can be the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 112 publications
7
78
0
4
Order By: Relevance
“…Additionally, about 60 percent of students said they would like to learn online after the pandemic. In turn, 70 percent of India's agricultural students declared readiness for remote learning during the pandemic [160]. They preferred to use smartphones for online learning and attended the recorded classes with quizzes at the end.…”
Section: Covid-19 Pandemic and Distance Teaching Realitymentioning
confidence: 99%
“…Additionally, about 60 percent of students said they would like to learn online after the pandemic. In turn, 70 percent of India's agricultural students declared readiness for remote learning during the pandemic [160]. They preferred to use smartphones for online learning and attended the recorded classes with quizzes at the end.…”
Section: Covid-19 Pandemic and Distance Teaching Realitymentioning
confidence: 99%
“…ICTs must be studied and analyzed by university students, as a sign of their potential in academic settings but, at the same time, to create critical attitudes in them regarding their power of influence, which today leads to many significant problems: addiction, alienation, irrational consumer, cyber-bullying, etc. (Lázaro et al, 2020;Gómez-Galán et al, 2020c). Moreover, in parallel, to the growing media manipulation taking place in today's society, of complex mechanisms as recently presented by Levitskaya and Fedorov (Levitskaya, Fedorov, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also suggest that we need to have a balanced perspective on monitoring ICT use while allowing users to take advantage of the technology [ 10 , 20 ]. Using social media has been regarded as a negative practice as there is evidence of addiction and excessive usage [ 41 , 42 ]. However, when it is used for staying socially engaged and connected during COVID-19, our finding showed that people had less negative feelings about the future.…”
Section: Discussionmentioning
confidence: 99%
“…Among a sample of adolescents and young adults across several countries, COVID-related worries, compulsive internet use, social media use, and gaming addiction predicted scores of escapism, depression, and loneliness [ 41 ]. A study conducted during June 2020 found that college students had excessive use of social networking sites and lack of personal control to disengage themselves from those sites [ 42 ]; this tendency was also associated with the use of alcohol, tobacco, cannabis, and sedative without a doctor’s prescription. Another study conducted in March and April 2020 in the U.S. suggested that exposure to COVID-19 information, via Twitter, Instagram, and Facebook, and increased alcohol use in March contributed to more frequent alcohol consumption in April, especially those working or studying from home [ 43 ].…”
Section: Literature Reviewmentioning
confidence: 99%